Analysis of the Flow of Registration of Bpjs Outpatient Igd Patients to Improve Service Quality at Rsud Bandung Kiwari - Dita Khairatin Nisaa; Erix Gunawan (MultiTech Publisher, 2024)
The number of BPJS patients at Bandung Kiwari Hospital has increased, and this needs to be considered in the quality of service. Often related to payment, the patient has been explained in detail the terms of payment at Bandung Kiwari Hospital but at the end, the patient does not comply with the terms of payment at the hospital this is a factor that becomes an obstacle, and makes the registration service process more delayed. The purpose of this study was to determine how the flow of registration of outpatient BPJS patients in the emergency room improves service quality at Bandung Kiwari Hospital. The research method used is a descriptive analysis method with a quantitative approach with 100 respondents, the majority aged 20-45 years. Primary data was collected through questionnaires, while secondary data through direct observation. The results showed that 84% of respondents agreed with the quality of registration services provided by officers to patients. The research instruments used stationery, mobile phones, and interview guidelines. Based on the Hospital SPO for emergency room registration for BPJS participants, it is explained that the patient must bring an identity card (KTP / KK / BPJS and the identity of the person in charge), but there are still patients/people in charge who forget or do not bring identity at all, besides that the hospital is lacking in conveying information to patients so that there are still patients lacking information for BPJS registration who must register with the BPJS.